The Influence of Destination Image and Customer Value toward Customer Loyalty through a Customer Satisfaction The Tourist District Guci Tegal. - Amalia, Ilda; Murwatiningsih, Murwatiningsih (Universitas Negeri Semarang, 2016)
The aims of this research are to analyze the direct and indirect influence of the destination image, customer value and customer satisfaction on the customer loyalty at the Guci Tour. The sample size consist of 100 respondents with incidental sampling through likert scale questionnaire. Percentage descriptive, multiple linier regression and path analysis were employed to analyze data. Results showed any effect of the image of the destination and the value of customer loyalty through customer satisfaction so that visitors can be said of a relationship mediation in this study. The conclusion of this research are proved that 1) the image of destinations has no direct influence on satisfaction and loyalty of visitors, 2) the image of the destination and visitor satisfaction as mediating indirect effect on the loyalty of visitors, 3) customer value and customer satisfaction as a mediating influence directly and indirectly to the visitor loyalty.